2003
DOI: 10.1128/ec.2.5.830-840.2003
|View full text |Cite
|
Sign up to set email alerts
|

trans and cis Splicing in Trypanosomatids: Mechanism, Factors, and Regulation

Abstract: mRNA maturation in trypanosomes differs from the process in most eukaryotes mainly because protein-coding genes are transcribed into polycistronic RNAs in this organism (78). Studies from the ongoing genome project suggest that the entire chromosome may be transcribed as large transcripts, but thus far there is no evidence to support the existence of conventional polymerase II promoters (62). The process of trans splicing was discovered 20 years ago when it was found that the different variant surface glycopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
263
0
15

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(278 citation statements)
references
References 112 publications
(151 reference statements)
0
263
0
15
Order By: Relevance
“…trans and cis RNA splicing, however, share several similarities. For example, at least some components of the cis RNA spliceosomes are conserved in T. brucei, and both cis and trans RNA splicing utilize the same general mechanism and require the same general sequence motifs [4]. During an examination of the effect of different 3′ UTRs on gene expression in T. brucei, we noticed differences between bloodstream form (BSF) and procyclic form (PCF) trypanosomes in the addition of SLs to RNAs transcribed from a luciferase reporter gene inserted into the rRNA gene locus.…”
mentioning
confidence: 99%
“…trans and cis RNA splicing, however, share several similarities. For example, at least some components of the cis RNA spliceosomes are conserved in T. brucei, and both cis and trans RNA splicing utilize the same general mechanism and require the same general sequence motifs [4]. During an examination of the effect of different 3′ UTRs on gene expression in T. brucei, we noticed differences between bloodstream form (BSF) and procyclic form (PCF) trypanosomes in the addition of SLs to RNAs transcribed from a luciferase reporter gene inserted into the rRNA gene locus.…”
mentioning
confidence: 99%
“…Once the polycistronic pre-mRNA is produced, the following two coupled reactions allow for the generation of mature monocistronic transcripts: trans-splicing and polyadenylation (Teixeira & DaRocha 2003). Every trypanosomatid mature mRNA possesses a SL sequence, which is a capped sequence that contains the same 39 nucleotides on the 5' end, and this SL is attached to the transcript in a process called transsplicing (Liang et al 2003). While no sequence consensus for polyadenylation or SL addition have been found in trypanosomatids, several studies have demonstrated that polypyrimidine-rich regions within intergenic regions guide SL addition and the polyadenylation of upstream and downstream genes, respectively, resulting in the generation of mature mRNAs (Hartmann et al 1998, López-Estraño et al 1998.…”
mentioning
confidence: 99%
“…In these segments, DNA elements involved in regulation of the gene expression and in the interaction with the new types of RNA (e.g., micro-RNA) have already been identified (Mignone et al 2002, Hughes 2006). For T. cruzi (and all trypanosomatids), most of the genes have no introns and the messenger RNA are processed by the mechanism of trans-splicing (Gull 2001, Liang et al 2003. In principle, the analysis of the transcripts in trypanosomatids could be easily accomplished, from the very moment that the respective sequences are available.…”
mentioning
confidence: 99%